2015
DOI: 10.1038/modpathol.2014.107
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of RET and ROS1 rearrangement in lung adenocarcinoma

Abstract: The success of crizotinib in ALK-positive patients has elicited efforts to find new oncogenic fusions in lung cancer. These efforts have led to the discovery of novel oncogenic fusion genes such as ROS1 and RET. However, the molecular and clinicopathologic characteristics associated with RET or ROS1 fusion, compared with ALK fusion-positive lung cancer, remain unclear. We accordingly analyzed the clinicopathologic characteristics of RET-and ROS1-fusion-positive lung adenocarcinomas. We further performed immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
114
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(123 citation statements)
references
References 34 publications
4
114
0
5
Order By: Relevance
“…This statement is evidence based and supported by 3 studies, 37,62,63 consisting of 1 PCS 62 and 2 RCSs. 37,63 All included studies were assessed for quality and none were found to have methodologic flaws that would raise concerns about the studies' findings (SDC Table 12). Refer to SDC Table 13 for a summary of findings from studies supporting the use of RET molecular testing.…”
Section: Expert Consensus Opinionmentioning
confidence: 65%
See 4 more Smart Citations
“…This statement is evidence based and supported by 3 studies, 37,62,63 consisting of 1 PCS 62 and 2 RCSs. 37,63 All included studies were assessed for quality and none were found to have methodologic flaws that would raise concerns about the studies' findings (SDC Table 12). Refer to SDC Table 13 for a summary of findings from studies supporting the use of RET molecular testing.…”
Section: Expert Consensus Opinionmentioning
confidence: 65%
“…30,37 However, this association has not been consistently observed across studies. 34 Other clinical characteristics, such as younger age, female sex, and non-Asian ethnicity, have been associated with ROS1 rearrangement in isolated studies only.…”
Section: Expert Consensus Opinionmentioning
confidence: 95%
See 3 more Smart Citations